EDUKASI PENGOLAHAN HASIL PERIKANAN DALAM UPAYA PENGUATAN PANGAN BERBASIS PROTEIN DI NEGERI TENGAH TENGAH, MALUKU TENGAH - Silaban, Bernita; Leiwakabessy, Jusuf; Tupan, Johanna; Lewerissa, Sherly; Nanlohy, Esterlina E.E. M.; Rieuwpassa, Fredrik (Jurnal Abdi Insani, 2024)
Country Tengah-Tengah is a coastal village characterized by a hilly highland topography, where the majority of the population are engaged in fishing as their primary livelihood. During times of abundant fish supply, all catches are typically sold in the market and are not retained for household consumption. However, when fish become scarce due to adverse weather conditions, the community tends to seek alternative protein sources such as tofu and tempeh as substitutes for fish, and some individuals even opt not to consume fish. There are also those who have a lesser preference for fish consumption. The aim of PKM is to provide education on fishery product processing as part of efforts to strengthen protein-based food security by introducing processed fish products. This is intended to enhance the community's understanding of the importance of fish consumption. The methods employed in this activity include lectures, discussions, and training sessions. Lectures are delivered in the form of power point presentations and leaflets, followed by question and answer sessions. The target audience comprises members of the PKK and housewives in County Tengah-Tengah, Central Maluku. Following the educational sessions, there was an increase in knowledge levels among the participants, transitioning from ignorance to awareness. Participants acknowledged their satisfaction with the wealth of information provided, covering topics such as the benefits of fish and its nutritional content, fish processing techniques, product diversification, preservation methods, quality control, surimi production, application of surimi in various fish products, and proper packaging techniques. It is expected that through this activity, the community will be able to produce surimi products according to their characteristics and be motivated to create diverse and high-quality processed fish products. This initiative aims to increase the added value of fish, address the scarcity of fish during certain seasons, and contribute to additional income generation for the residents of Country Tengah-Tengah.